Is time running out? The urgent need for appropriate global health curricula in Germany. Issue 11 (19th November 2020) - Schuster, Angela; Anton, Nora; Grosse, Pascal; Heintze, Christoph
Abstract : Recently, representatives of politics, health officials and academia in Germany have advocated a greater role for Germany in matters concerning global health. However, health professionals in Germany are rarely taught about global health topics and accordingly real expertise in this field is lacking. To advance knowledge and competencies at German universities and adequately equip health professionals to achieve Germany's political goals, global health curricula must be developed at medical schools and other institutions. Such ambitions raise questions about the required content and dimensions of global health curricula as the field is currently highly heterogeneous and ill defined. To systematically identify strengths and shortcomings of current curricula, we scrutinised the global health curriculum at our institution, Charité—Universitätsmedizin Berlin, using an analytical framework that integrates the various approaches of global health. Our analysis identified that four (technical, social justice, security and humanitarian) of five approaches are present in our core global health curriculum. Local and global aspects of the field are equally represented. We propose that the use of such a structured analytical framework can support the development of GH curricula for all health professionals—in Germany and elsewhere. But it can also help to evaluate existing curricula like ours at Charité. This framework has the potential to support the design of comprehensive GH trainings, serving German aspirations in politics and academia to promote health worldwide.